Buffer management for active reliable multicast - Zhang, Jingyu (2008)
Reliable multicast over the Internet is difficult with a number of problems such as NACK implosion, distributed loss recovery, retransmission scoping, etc. Active Reliable Multicast (ARM), a novel loss recovery scheme for large-scale reliable multicast, utilizes soft-state storage (intermediate routers) within the network to cache data for local retransmission, to suppress duplicate NACKs and to perform scoped retransmission. In the heterogeneous Internet, some links are reliable while some are relatively unreliable. ARM mechanisms need to deal with this heterogeneity. In ARM. how to utilize the active resources efficiently for packet loss recovery is an important issue. A more efficient and fair buffer scheme could provide a better solution.